STRATEGIC COMMUNICATION MUSEUM KERETA API AMBARAWA CREATIVE MANAGER - Aditya Iman Hamidi; Tandiyo Pradekso; M Bayu Widagdo; Djoko Setyabudi (Interaksi Online, 2015)
This project in based on the less promotion Ambarawa Train Museum as an thepotential tourism assets that owned by PT Kereta Api Indonesia which located inCentral Java. Less promotion doesn’t make a lot of visitors who come to AmbarawaTrain Museum. In this project, Creative Manager has a purpose to promote theAmbarawa Train Museum through graphic design for publication and merchandisebased on Visual Communication Design concept. Creative Manager also responsiblewith finding talent to perform at the museum in order to increase the attractiveness ofthe visitors. These activities raised in a series of activities Strategic CommunicationAmbarawa Train Museum in order to increase knowledge of public and visitors to themuseum.The project is held in one month. In the main events earned 5 talents with detail3 traditional performer and 2 modern performer The result from promotion throughgraphic design for publication and merchandise earned a positive respon from publicindicated by teh increasing visitor who come to the museum in May which significantlyby 30.786 visitors, where in previous month no more than 10,000 visitors. In addition,this project shows that the Strategic Communication Ambarawa Train Museum"Sepoorheroes" was successful.